On The Characterizations of The Interval Sequential Equal Contributions Rule - Sırma ALPARSLAN GÖK (Süleyman Demirel Üniversitesi Fen-Edebiyat Fakültesi Fen Dergisi, 2015)
Abstract: This paper deals with the research area of cooperative interval games arising from airport situations with interval data. The major topic of the paper is to present and introduce the interval sequential equal contributions rule. The main result of this study is to give an axiomatic characterization of the interval sequential equal contributions rule. Key words: airport situations, sequential equal contributions rule, interval data.